CASE REPORT: INNOVATIVE TREATMENT OF CUTANEOUS LARVA MIGRANS MANAGEMENT - Sukmawati Tansil Tan; Yohanes Firmansyah; Yurike Indah Pratiwi (Yayasan Pendidikan Medika Indonesia, 2021)
Cutaneous larva migrans (CLM) is a skin infection caused by nematode larvae that penetrate actively and migrate within the epidermis of the skin. Several reports from the livestock sector report that resistance mechanisms are emerging due to the irrational use of anti-helminths. This case report describes a case of CLM that was treated with a new approach of using 5% permethrin cream topically for ten days (empirical therapy generally consists of Albendazole and Ivermectin with high resistance rates in animals). The 5% permethrin cream treatment effectively treats